A New Methodology for Active Power Transmission Loss Allocation in Deregulated Power System - Prakash Kumar Hota; Atulya Prasad Naik (Institute of Advanced Engineering and Science, 2017)
This paper presents a new method for transmission loss allocation in a deregulated power system. As the power loss is a nonlinear quantity, so to allocate the loss in a common transmission corrider is a difficult task. It allocates transmission losses to loads based on the actual power flow in the lossy lines due to the concerned load. Each lossy line is subdivided into as many sub-lines as corresponding to the numbers of load attached to it. The tracing of power flow through each sub-line is worked out by using proportional sharing method. The power loss in each lossy line is equal with the total loss due to all the sub-lines under it. Then by using Pro-rata for each lossy line, the individual loss for each sub-line is formulated. As the application of Pro-rata is limited to an individual line of the system, so the error in calculation is minimized. The total loss allocated to a particular load is the sum of losses occurred in each lossy lines through which the power is flowing to the concerned load. As this method is based on the actual flow of power in the transmission line corresponding to the concerned load, hence, the loss allocation made by the method gives proper and justifiable allocations to the different loads which are attached to the system. The proposed method is applied to a six-bus system and finds the mismatch in the commonly used methods. Then, it is applied to higher bus systems in which more accurate results are obtained compared to the other methods.